Sleep quality and well-being in obesity-hypoventilation syndrome versus obstructive sleep apnea with obesity: A comparative study - Vasiliki Epameinondas Georgakopoulou; Athina Lazaridou; Athanasios Voulgaris; Kostas Archontogeorgis; Maria Dalamaga; Evangelia Nena; Paschalis Steiropoulos (Metabolism Open)
Background: Only a few studies in the published literature have assessed the well-being, and the sleep quality (SQ) in patients with obesity hypoventilation syndrome (OHS). The aim of this study was to evaluate well-being and SQ in patients with OHS and to compare these outcomes with those of patients with obstructive sleep apnea (OSA) and obesity. Methods: Consecutive subjects being referred for evaluation of sleep disordered breathing were enrolled in the study. Patients were divided into two groups: Group A: OSA patients with BMI ≥30 kg/m2 and 2) Group B: OHS patients. Well-being was assessed using the World Health Organization-Five Well-Being Index (WHO-5), while sleep quality was evaluated using the Pittsburgh Sleep Quality Index (PSQI). Results: In total 1010 participants (OHS, n = 203) were included in the study. No difference was observed between groups in mean scores of Epworth Sleepiness Scale (ESS), Fatigue Severity Scale (FSS), WHO-5, and PSQI questionnaires. In patients with OHS, WHO-5 score was negatively correlated with neck circumference (r = −0.703, p = 0.016) and waist circumference (r = −0.728, p = 0.011). Moreover, PSQI scores in this group were significantly correlated with BMI (r = 0.410, p = 0.038). A lower WHO-5 score was observed in OHS patients with diabetes mellitus compared to non-diabetic patients with OHS (p = 0.049). Conclusions: Patients with OSA and OHS reported similarly poor well-being and SQ. In patients with OHS, both high neck - and waist circumference were associated with poor well-being, while higher BMI was associated with worse sleep quality. Additionally, the well-being of OHS patients with concomitant diabetes mellitus was worse compared to OHS patients without diabetes mellitus.